Children's Health Literacy in Relation to Their BMI z-Score, Food Intake, and Physical Activity: A Cross-Sectional Study among 8-11-Year-Old Children in The Netherlands - Jany Rademakers; Marla T. H. Hahnraths; Onno C. P. van Schayck; Monique Heijmans (MDPI AG, 2022)
Overweight and obesity in children are an increasing public health problem. Health literacy (HL) is a determinant of obesity and body mass index (BMI) rates in adults, but few studies have addressed the impact of children's own HL on their weight and lifestyle. In this study, we aim to assess the impact of Dutch children's HL on (1) their BMI z-score, (2) dietary behaviour, and (3) the amount of physical activity (PA) they engage in. A sample of 139 children (age 8-11 years) filled out a digital questionnaire, including an HL measurement instrument and questions regarding their food intake and PA. Furthermore, the height and weight of the children were measured, and background information was collected using a parental questionnaire. Multiple regression revealed a significant positive relation between children's HL and their PA. No significant association between children's HL and their BMI z-score or dietary behaviour was found. HL of children in primary school thus has an impact on some aspects of children's lifestyle, although more research in a larger, more diverse sample is needed to further investigate this.